2021
DOI: 10.14453/aabfj.v15i2.3
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Retail Investors’ Trading Behaviour in the Thai Stock Market

Abstract: This paper investigates trading behaviour among Thai retail investors in 2016. Using detailed survey data from 491 investors, we examine the characteristics and behavioural patterns that lead to investor bias. Empirical results in the behavioural finance literature indicate that retail investors may not behave reasonably. Behavioural biases may influence investor decisions and affect financial markets. These studies, however, are limited to subsamples of the overall investor groups studied and mainly focus on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 24 publications
(45 reference statements)
2
12
0
Order By: Relevance
“…If the stocks' price plummets, they will hold the loser asset and expect the price to be corrected. For this decision, overconfidence bias could be caused (Barber & Odean, 2001;Kinari, 2016;Paisarn et al, 2021). Therefore, the emotion of disappointment and overconfidence is the concept of perceived emotion observed in this research.…”
Section: Hypothesis Developmentmentioning
confidence: 73%
See 3 more Smart Citations
“…If the stocks' price plummets, they will hold the loser asset and expect the price to be corrected. For this decision, overconfidence bias could be caused (Barber & Odean, 2001;Kinari, 2016;Paisarn et al, 2021). Therefore, the emotion of disappointment and overconfidence is the concept of perceived emotion observed in this research.…”
Section: Hypothesis Developmentmentioning
confidence: 73%
“…The simulation approach could enhance the perceived emotion in investment, but knowing these feelings (disappointment and overconfidence) is not enough to avoid emotional bias in the investment decision. Retail investors are usually prone to emotional bias (Paisarn et al, 2021;Zahera & Bansal, 2018) evolved into fear of missing out as social media information drives their investment decision (Shiva et al, 2020). Specifically, in behavioural finance, two emotional biases related to this research are regret aversion and overconfidence bias, which are well documented in empirical findings (Fishburn, 2013;Jain et al, 2021;Quaicoe & Eleke-Aboagye, 2021;Shah & Malik, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…journal.ump.edu.my/ijim ◄ Financial behaviour aspect can be determined by several indicators. For example, Paisarn et. al (2021) indicated that demographic factors such as gender, years of experience in trading, age, and income play their roles in shaping trading behaviour amongst stock market investors.…”
Section: Introductionmentioning
confidence: 99%